Method for preparing polyketone fiber by wet spinning
By blending polyketone with pyrrole copolymer, modified multi-wall carbon nanotube and other materials and multi-stage thermal stretching process, the polyketone fibers prepared by wet spinning are easily broken, have low strength and low thermal stability, and the performance of the fiber is significantly improved.
Patent Information
- Application Number
- CN202411672497.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyketone fibers prepared by wet spinning method using organic solvents in the prior art are prone to breaking wires, with low fiber strength, low thermal stability and low toughness.
Polyketone blends were prepared by high-speed stirring of polyketone, pyrrole copolymer, modified multi-wall carbon nanotubes, thermoplastic polyurethane, phenyl alkyl sulfonate T50 and powdered phosphite, and double-screw extrusion granulation, and polyketone fibers were prepared by wet spinning and multi-stage thermal stretching processes.
It effectively reduces the filament breaking rate of polyketone fibers, improves its tensile strength, elongation rate of breaking and thermal stability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyketone fibers, and in particular relates to a method for preparing polyketone fibers by wet spinning. Background Art
[0002] Polyketone is made from carbon monoxide and α-olefins (such as ethylene and propylene) using a one-step catalytic production process. The produced polymer has the characteristics of high melting point, semi-crystalline and complete alternating chain structure. Compared with semi-crystalline engineering thermoplastics made of other materials, polyketone has good impact resistance, chemical resistance, wear resistance and good hydrolytic stability. The linear and complete alternating chain structure of polyketone gives it unique properties. When used to make fibers, the fibers have very high strength.
[0003] Polyketone is unstable in high temperature environment, and is prone to intramolecular and intermolecular cross-linking to generate furan rings or aldol condensation reaction, causing polymer denaturation. In the manufacturing process of polyketone fiber, a small amount of polymer denaturation can cause burrs and broken wires during heat stretching. When the polymer denaturation range increases, it will also lead to a decrease in tensile strength and elongation. At the same time, polyketone is also prone to denaturation in oxidative, acidic and alkaline environments.
[0004] Since polyketone deteriorates violently in the molten state, it is difficult to carry out melt spinning. Therefore, the method of fiberization of polyketone generally adopts a wet spinning method in which polyketone is dissolved in a solvent for fiber formation. The solvents used for preparing polyketone fibers by wet spinning include inorganic solvents and organic solvents. Compared with inorganic solvents, the solubility of polyketone is high when organic solvents are used, the temperature required for dissolution is low, the solution viscosity is low, and the solution stability is high. At the same time, the adverse effects of residual metal ions in inorganic solvents on polyketone fibers in applications such as rubber can be avoided. In the organic solvent dissolution step of wet spinning, and in the high-temperature stretching step of polyketone fibers with a small amount of organic solvent remaining, denaturation phenomena such as intramolecular and intermolecular crosslinking of polyketone are prone to occur, resulting in a large number of broken fibers in the obtained fibers, reduced fiber strength, and problems such as reduced thermal stability and reduced toughness. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing polyketone fibers by wet spinning, which solves the problems of easy breakage of polyketone fibers prepared by wet spinning using organic solvents, low fiber strength, low thermal stability, and low toughness.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing polyketone fiber by wet spinning, characterized in that the method for preparing polyketone fiber by wet spinning comprises the following steps: preparation of raw materials, preparation of spinning solution, spinning, and stretching; The preparation of the raw materials comprises adding polyketone, pyrrole copolymer, modified multi-walled carbon nanotubes, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50 and powdered phosphite into a high-speed mixer, controlling the stirring temperature to be 130-140° C., stirring at a speed of 800-1000 rpm for 8-10 minutes and then releasing the mixture, and then extruding and granulating the mixture in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1-1.5 dl / g; The mass ratio of the polyketone, pyrrole copolymer, modified multi-walled carbon nanotube, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50 and powdered phosphite is 100: (5-7): (2-3): (3-5): (0.5-0.8): (0.6-0.8).
[0007] The preparation of the pyrrole copolymer includes preparing N-vinyl pyrrole, copolymerizing; In the preparation of N-vinyl pyrrole, sodium hydroxide is dissolved in dimethyl sulfoxide to prepare a 160-170 g / L sodium hydroxide solution, the solution is heated to a temperature of 50-55° C., pyrrole is added at this temperature, and 1,2-dichloroethane is added dropwise after stirring for 10-12 minutes. After the addition is completed, the solution temperature is raised to 95-100° C., and stirring is continued for 14-16 hours. After the reaction is completed, a fraction in the range of 92-96° C. is obtained by atmospheric distillation, and the fraction is N-vinyl pyrrole; The mass ratio of the pyrrole, 1,2-dichloroethane and sodium hydroxide solution is (10-12): (20-25): 200.
[0008] The copolymerization comprises dissolving sodium perfluorononenyloxybenzenesulfonate in a 40-45 g / L hydrochloric acid solution to prepare a sodium perfluorononenyloxybenzenesulfonate solution with a concentration of 220-230 g / L, then adding N-vinyl pyrrole and pyrrole, stirring for 30-40 min, introducing ethylene at a rate of 0.2-0.3 L / min, and simultaneously dropping a 25-30 g / L ferric chloride solution acidified with hydrochloric acid, continuously stirring and reacting for 24-26 h under ice bath conditions, washing the sample with water for 3-4 times after the reaction is completed, and freeze-drying to constant weight to obtain a pyrrole copolymer; The pH of the ferric chloride solution acidified by hydrochloric acid is 1.8-2; The mass ratio of N-vinylpyrrole, pyrrole, ethylene, sodium perfluorononenyloxybenzenesulfonate and ferric chloride is (8-10): (10-12): (2-3): (18-20): (100-120).
[0009] The preparation of the modified multi-walled carbon nanotubes comprises dissolving N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes and p-toluenesulfonic acid in cyclohexanone, ultrasonically oscillating for 20-25 minutes at a frequency of 10-12 kHz, then heating to 90-95° C., stirring and reacting at the temperature for 10-12 hours, filtering, washing the filter cake with an ethanol-water mixture for 3-5 times, and drying at 50-55° C. for 10-12 hours to obtain the modified multi-walled carbon nanotubes; The mass ratio of N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes, p-toluenesulfonic acid and cyclohexanone is (6-8): (3-4): (40-50): (0.3-0.5): 100; The volume ratio of ethanol to water in the ethanol-water mixture is 1:(4-5).
[0010] The spinning solution is prepared by adding a polyketone blend into a dimethyl sulfoxide solvent to make the polyketone blend have a concentration of 10-12 wt %, stirring and dissolving at 30-35° C. for 30-40 min, degassing under reduced pressure and stirring for 6-7 h, and filtering at 30-35° C. after stirring to obtain the spinning solution.
[0011] In the spinning, the spinning solution is introduced into the spinning assembly by a metering pump, the ejected spinning solution is introduced into a coagulation bath to coagulate into fibers, and the collected fibers are then washed and dried with ethanol to obtain primary fibers; The spinning solution temperature is 90-95°C, the coagulation bath is a mixture of dimethyl sulfoxide and water in a mass ratio of 1: (4-5), and the coagulation bath temperature is 5-8°C.
[0012] The stretching comprises: performing heat stretching on the spun fiber in three stages, controlling the temperature of the primary stretching to be 238-242° C., and the stretching ratio to be 6-7 times; performing secondary stretching after the primary stretching, controlling the temperature of the secondary stretching to be 248-252° C., and the stretching ratio to be 2-2.5 times; performing tertiary stretching after the secondary stretching, controlling the temperature of the tertiary stretching to be 258-262° C., and the stretching ratio to be 1.5-1.8 times; and obtaining polyketone fiber after the tertiary stretching; The fineness of the prepared polyketone fibers is 1.5-1.8 dtex.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The polyketone fiber prepared by the method of the present invention effectively reduces the broken wire rate of the polyketone fiber and improves its tensile strength, elongation at break and thermal stability. The broken wire rate of the prepared polyketone fiber is reduced to 0.4-0.5%, the tensile strength is 20.1-20.4 cN / dtex, the elongation at break is 45-48%, and the tensile strength reduction rate after heat treatment is 6.86-7.46%. DETAILED DESCRIPTION
[0014] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0015] Example 1 A method for preparing polyketone fiber by wet spinning, comprising the following steps: preparing raw materials, preparing spinning solution, spinning, and stretching; (1) Preparation of raw materials Add polyketone, pyrrole copolymer, modified multi-walled carbon nanotube, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite into a high-speed mixer, control the stirring temperature to be 130° C., stir at a speed of 800 rpm for 10 minutes, then release, and extrude and granulate the mixture in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1 dl / g; The mass ratio of the polyketone, the pyrrole copolymer, the modified multi-walled carbon nanotube, the thermoplastic polyurethane, the alkyl sulfonate phenyl ester T50, and the powdered phosphite is 100:5:2:3:0.5:0.6.
[0016] The preparation of the pyrrole copolymer comprises the following steps: A. Preparation of N-vinylpyrrole Sodium hydroxide is dissolved in dimethyl sulfoxide to prepare a 160 g / L sodium hydroxide solution, and the solution is heated to a temperature of 50°C. Pyrrole is added at this temperature, and 1,2-dichloroethane is added dropwise after stirring for 12 minutes. After the addition is completed, the solution temperature is raised to 95°C and stirring is continued for 16 hours. After the reaction is completed, a fraction within the range of 92°C-96°C is obtained by atmospheric distillation, which is N-vinyl pyrrole; The mass ratio of the pyrrole, 1,2-dichloroethane and sodium hydroxide solution is 10:20:200.
[0017] B. Copolymerization Sodium perfluorononenyloxybenzenesulfonate was dissolved in 40 g / L hydrochloric acid solution to prepare a sodium perfluorononenyloxybenzenesulfonate solution with a concentration of 220 g / L. N-vinylpyrrole and pyrrole were then added. After stirring for 30 min, ethylene was introduced at 0.2 L / min. At the same time, a 25 g / L ferric chloride solution acidified with hydrochloric acid was added dropwise. The reaction was stirred for 24 h under ice bath conditions. After the reaction was completed, the sample was washed with water 3 times and freeze-dried to constant weight to obtain a pyrrole copolymer.
[0018] The mass ratio of N-vinylpyrrole, pyrrole, ethylene, sodium perfluorononenyloxybenzenesulfonate, and ferric chloride is 8:10:2:18:100; The pH of the ferric chloride solution acidified with hydrochloric acid is 2.
[0019] The preparation of the modified multi-walled carbon nanotubes comprises dissolving N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes and p-toluenesulfonic acid in cyclohexanone, ultrasonically vibrating for 20 minutes at a frequency of 10 kHz, then heating to 90° C., stirring and reacting at this temperature for 12 hours, filtering, washing the filter cake with an ethanol-water mixture for three times, and drying at 50° C. for 12 hours to obtain the modified multi-walled carbon nanotubes; The mass ratio of the N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes, p-toluenesulfonic acid and cyclohexanone is 6:3:40:0.3:100; The volume ratio of ethanol to water in the ethanol-water mixture is 1:4.
[0020] (2) Preparation of spinning solution The polyketone blend was added into dimethyl sulfoxide solvent to make the concentration of the polyketone blend 10wt%, and dissolved by stirring at 30°C for 30min, degassed under reduced pressure and stirred for 6h, and filtered at 30°C after stirring to obtain a spinning solution.
[0021] (3) Spinning The spinning solution is introduced into the spinning assembly by a metering pump, and the ejected spinning solution is introduced into a coagulation bath to coagulate into fibers, and then the collected fibers are washed and dried with ethanol to obtain primary fibers; The spinning solution temperature was controlled at 90°C, the coagulation bath was a mixture of dimethyl sulfoxide and water in a mass ratio of 1:4, and the temperature of the coagulation bath was 5°C.
[0022] (4) Stretching The spun fiber is heat-stretched in three stages, the temperature of the first stage drawing is controlled at 238°C, the drawing ratio is 6 times, the second stage drawing is performed after the first stage drawing, the temperature of the second stage drawing is controlled at 248°C, the drawing ratio is 2 times, the temperature of the third stage drawing is controlled at 258°C, the drawing ratio is 1.5 times, and the polyketone fiber is obtained after the third stage drawing; The fineness of the prepared polyketone fibers was 1.8 dtex.
[0023] Example 2 A method for preparing polyketone fiber by wet spinning, comprising the following steps: preparing raw materials, preparing spinning solution, spinning, and stretching; (1) Preparation of raw materials Add polyketone, pyrrole copolymer, modified multi-walled carbon nanotube, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite into a high-speed mixer, control the stirring temperature to be 135° C., stir at a speed of 900 rpm for 9 minutes, then release, and extrude and granulate the mixture in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1.2 dl / g; The mass ratio of the polyketone, the pyrrole copolymer, the modified multi-walled carbon nanotube, the thermoplastic polyurethane, the alkyl sulfonate phenyl ester T50, and the powdered phosphite is 100:6:2.5:4:0.6:0.7.
[0024] The preparation of the pyrrole copolymer comprises the following steps: A. Preparation of N-vinylpyrrole Sodium hydroxide was dissolved in dimethyl sulfoxide to prepare a 165 g / L sodium hydroxide solution, and the solution was heated to a temperature of 52°C. Pyrrole was added at this temperature, and 1,2-dichloroethane was added dropwise after stirring for 11 minutes. After the addition was completed, the solution temperature was raised to 98°C and the stirring was continued for 15 hours. After the reaction was completed, the fraction within the range of 92°C-96°C was obtained by atmospheric distillation, which was N-vinyl pyrrole; The mass ratio of the pyrrole, 1,2-dichloroethane and sodium hydroxide solution is 11:22:200.
[0025] B. Copolymerization Sodium perfluorononenyloxybenzenesulfonate was dissolved in 42 g / L hydrochloric acid solution to prepare a sodium perfluorononenyloxybenzenesulfonate solution with a concentration of 225 g / L. N-vinylpyrrole and pyrrole were then added. After stirring for 35 min, ethylene was introduced at 0.25 L / min. At the same time, a 28 g / L ferric chloride solution acidified with hydrochloric acid was added dropwise. The reaction was stirred for 25 h under ice bath conditions. After the reaction was completed, the sample was washed with water 4 times and freeze-dried to constant weight to obtain a pyrrole copolymer.
[0026] The mass ratio of N-vinylpyrrole, pyrrole, ethylene, sodium perfluorononenyloxybenzenesulfonate, and ferric chloride is 9:11:2.5:19:110; The pH of the ferric chloride solution acidified with hydrochloric acid is 2.
[0027] The preparation of the modified multi-walled carbon nanotubes comprises dissolving N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes and p-toluenesulfonic acid in cyclohexanone, ultrasonically vibrating for 22 minutes at a frequency of 11 kHz, then heating to 92° C., stirring and reacting at this temperature for 11 hours, filtering, washing the filter cake with an ethanol-water mixture for 4 times, and drying at 50° C. for 11 hours to obtain the modified multi-walled carbon nanotubes; The mass ratio of N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes, p-toluenesulfonic acid and cyclohexanone is 7:3.5:45:0.4:100; The volume ratio of ethanol to water in the ethanol-water mixture is 1:4.
[0028] (2) Preparation of spinning solution The polyketone blend was added into dimethyl sulfoxide solvent to make the concentration of the polyketone blend 11 wt %. The mixture was dissolved by stirring at 32° C. for 33 min, degassed under reduced pressure and stirred for 6.5 h. After stirring, the mixture was filtered at 32° C. to obtain a spinning solution.
[0029] (3) Spinning The spinning solution is introduced into the spinning assembly by a metering pump, and the ejected spinning solution is introduced into a coagulation bath to coagulate into fibers, and then the collected fibers are washed and dried with ethanol to obtain primary fibers; The spinning solution temperature was controlled at 92°C, the coagulation bath was a mixture of dimethyl sulfoxide and water in a mass ratio of 1:4, and the temperature of the coagulation bath was 6°C.
[0030] (4) Stretching The spun fiber is heat-stretched in three stages, the temperature of the first stage drawing is controlled at 240°C, the drawing ratio is 6.5 times, the second stage drawing is performed after the first stage drawing, the temperature of the second stage drawing is controlled at 250°C, the drawing ratio is 2.2 times, the temperature of the third stage drawing is controlled at 260°C, the drawing ratio is 1.6 times, and the polyketone fiber is obtained after the third stage drawing; The fineness of the prepared polyketone fibers was 1.6 dtex.
[0031] Example 3 A method for preparing polyketone fiber by wet spinning, comprising the following steps: preparing raw materials, preparing spinning solution, spinning, and stretching; (1) Preparation of raw materials Add polyketone, pyrrole copolymer, modified multi-walled carbon nanotube, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite into a high-speed mixer, control the stirring temperature to be 140° C., stir at a speed of 1000 rpm for 8 minutes, then release, and extrude and granulate the mixture in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1.5 dl / g; The mass ratio of the polyketone, the pyrrole copolymer, the modified multi-walled carbon nanotube, the thermoplastic polyurethane, the alkyl sulfonate phenyl ester T50, and the powdered phosphite is 100:7:3:5:0.8:0.8.
[0032] The preparation of the pyrrole copolymer comprises the following steps: A. Preparation of N-vinylpyrrole Sodium hydroxide is dissolved in dimethyl sulfoxide to prepare a 170 g / L sodium hydroxide solution, and the solution is heated to a temperature of 55°C. Pyrrole is added at this temperature, and 1,2-dichloroethane is added dropwise after stirring for 10 minutes. After the addition is complete, the solution temperature is raised to 100°C, and stirring is continued for 14 hours. After the reaction is completed, a fraction within the range of 92°C-96°C is obtained by atmospheric distillation, which is N-vinyl pyrrole; The mass ratio of the pyrrole, 1,2-dichloroethane and sodium hydroxide solution is 12:25:200.
[0033] B. Copolymerization Sodium perfluorononenyloxybenzenesulfonate was dissolved in 45 g / L hydrochloric acid solution to prepare a sodium perfluorononenyloxybenzenesulfonate solution with a concentration of 230 g / L. N-vinylpyrrole and pyrrole were then added. After stirring for 40 min, ethylene was introduced at 0.3 L / min. At the same time, a 30 g / L ferric chloride solution acidified with hydrochloric acid was added dropwise. The reaction was stirred for 26 h under ice bath conditions. After the reaction was completed, the sample was washed with water 4 times and freeze-dried to constant weight to obtain a pyrrole copolymer.
[0034] The mass ratio of N-vinylpyrrole, pyrrole, ethylene, sodium perfluorononenyloxybenzenesulfonate, and ferric chloride is 10:12:3:20:120; The pH of the ferric chloride solution acidified with hydrochloric acid is 1.8.
[0035] The preparation of the modified multi-walled carbon nanotubes comprises dissolving N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes and p-toluenesulfonic acid in cyclohexanone, ultrasonically vibrating for 25 minutes at a frequency of 12 kHz, then heating to 95° C., stirring and reacting at this temperature for 10 hours, filtering, washing the filter cake with an ethanol-water mixture for 5 times, and drying at 55° C. for 10 hours to obtain the modified multi-walled carbon nanotubes; The mass ratio of N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes, p-toluenesulfonic acid and cyclohexanone is 8:4:50:0.5:100; The volume ratio of ethanol to water in the ethanol-water mixture is 1:5.
[0036] (2) Preparation of spinning solution The polyketone blend was added into dimethyl sulfoxide solvent to make the concentration of the polyketone blend 12 wt %. The mixture was dissolved by stirring at 35° C. for 40 min, degassed under reduced pressure and stirred for 7 h. After stirring, the mixture was filtered at 35° C. to obtain a spinning solution.
[0037] (3) Spinning The spinning solution is introduced into the spinning assembly by a metering pump, and the ejected spinning solution is introduced into a coagulation bath to coagulate into fibers, and then the collected fibers are washed and dried with ethanol to obtain primary fibers; The spinning solution temperature was controlled at 95°C, the coagulation bath was a mixture of dimethyl sulfoxide and water in a mass ratio of 1:5, and the temperature of the coagulation bath was 8°C.
[0038] (4) Stretching The spun fiber is heat-stretched in three stages, the temperature of the first stage drawing is controlled at 242°C, the drawing ratio is 7 times, the second stage drawing is performed after the first stage drawing, the temperature of the second stage drawing is controlled at 252°C, the drawing ratio is 2.5 times, the temperature of the third stage drawing is controlled at 262°C, the drawing ratio is 1.8 times, and the polyketone fiber is obtained after the third stage drawing; The fineness of the prepared polyketone fibers was 1.5 dtex.
[0039] Comparative Example 1 Comparative Example 1 The method for preparing polyketone fiber by wet spinning described in Example 2 is adopted, except that, in the step of preparing raw materials, the addition of pyrrole copolymer is omitted, and the step of preparing raw materials is changed to adding polyketone, modified multi-walled carbon nanotubes, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite into a mixer, the stirring process temperature is controlled to be 135° C., the mixture is stirred at a speed of 900 rpm for 9 minutes and then released, and then the mixture is extruded and granulated in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1.2 dl / g; The mass ratio of the polyketone, the modified multi-walled carbon nanotube, the thermoplastic polyurethane, the alkyl sulfonate phenyl ester T50, and the powdered phosphite is 100:2.5:4:0.6:0.7.
[0040] Comparative Example 2 Comparative Example 2 The method for preparing polyketone fiber by wet spinning described in Example 2 is adopted, except that in the step of preparing raw materials, the addition of sodium perfluorononenyloxybenzenesulfonate and ethylene is omitted in the preparation method of pyrrole copolymer, and the preparation method of pyrrole copolymer is changed to: The preparation of the pyrrole copolymer comprises the following steps: A. Preparation of N-vinylpyrrole Sodium hydroxide was dissolved in dimethyl sulfoxide to prepare a 165 g / L sodium hydroxide solution, and the solution was heated to a temperature of 52°C. Pyrrole was added at this temperature, and 1,2-dichloroethane was added dropwise after stirring for 11 minutes. After the addition was completed, the solution temperature was raised to 98°C and the stirring was continued for 15 hours. After the reaction was completed, the fraction within the range of 92°C-96°C was obtained by atmospheric distillation, which was N-vinyl pyrrole; The mass ratio of pyrrole, 1,2-dichloroethane and sodium hydroxide solution is 11:22:200; B. Copolymerization N-vinylpyrrole and pyrrole were added to a 42 g / L hydrochloric acid solution, stirred for 35 min, and then a 28 g / L ferric chloride solution acidified with hydrochloric acid was added dropwise. The reaction was stirred for 25 h under ice bath conditions. After the reaction, the sample was washed 4 times with water and freeze-dried to constant weight to obtain a pyrrole copolymer.
[0041] The mass ratio of N-vinylpyrrole, pyrrole, and ferric chloride is 9:11:110; The pH of the ferric chloride solution acidified with hydrochloric acid is 2.
[0042] Comparative Example 3 Comparative Example 1 The method for preparing polyketone fibers by wet spinning described in Example 2 is adopted, except that, in the step of preparing raw materials, the addition of modified multi-walled carbon nanotubes is omitted, and the step of preparing raw materials is changed to adding polyketone, pyrrole copolymer, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite into a mixer, controlling the stirring process temperature to 135° C., stirring at a speed of 900 rpm for 9 min, and then extruding and granulating the mixture in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1.2 dl / g; The mass ratio of the polyketone, the pyrrole copolymer, the thermoplastic polyurethane, the alkyl sulfonate phenyl ester T50, and the powdered phosphite is 100:6:4:0.6:0.7.
[0043] Comparative Example 4 Comparative Example 1 The method for preparing polyketone fibers by wet spinning described in Example 2 is adopted, except that, in the step of preparing raw materials, multi-walled carbon nanotubes are used instead of modified multi-walled carbon nanotubes, and the step of preparing raw materials is changed to adding polyketone, pyrrole copolymer, multi-walled carbon nanotubes, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite into a high-speed mixer, controlling the stirring process temperature to 135° C., stirring at a speed of 900 rpm for 9 minutes and then releasing, and then extruding and granulating the mixture in a twin-screw extruder to obtain a polyketone blend; The intrinsic viscosity [η] of the polyketone is 1.2 dl / g; The mass ratio of the polyketone, the pyrrole copolymer, the multi-walled carbon nanotube, the thermoplastic polyurethane, the alkyl sulfonate phenyl ester T50, and the powdered phosphite is 100:6:2.5:4:0.6:0.7.
[0044] Test Example 1 The broken wire rate, tensile strength and elongation at break of the polyketone fibers prepared in Examples 1-3 and Comparative Examples 1-4 were tested, and the test results are as follows:
[0045] It can be seen from the test results of Experimental Example 1 that the broken fiber rate of the polyketone fiber prepared in Comparative Example 1 is significantly higher than that in Example 2, and the tensile strength and elongation at break are significantly lower than those in Example 2; and in Comparative Example 2 using a pyrrole copolymer different from that in Example 2, the broken fiber rate is slightly decreased, and the tensile strength and elongation at break are increased to a small extent, indicating that the use of the homemade pyrrole copolymer of the present invention can reduce the broken fiber rate of the polyketone fiber and improve the tensile strength and elongation at break.
[0046] The polyketone blend of the present invention includes a homemade pyrrole copolymer, which is copolymerized by N-vinylpyrrole, pyrrole and ethylene in the presence of sodium perfluorononenyloxybenzenesulfonate. The presence of sodium perfluorononenyloxybenzenesulfonate can improve the order of the pyrrole copolymer, so that the pyrrole copolymer can be well fused with the polyketone; the present invention adopts ethylene and N-vinylpyrrole, pyrrole copolymer to prepare the pyrrole copolymer, and the addition of ethylene can change the structure of the pyrrole copolymer, so that the pyrrole copolymer can be completely dissolved in the dimethyl sulfoxide solvent, and the polyketone blend containing the pyrrole copolymer can be smoothly wet-spun. The pyrrole copolymer contains a π electron conjugated system and an imino group, which can form a strong interaction with the polyketone and cause the entanglement of the molecular chain. The moderate molecular chain entanglement effectively blocks the cross-linking reaction of the polyketone intramolecular and intermolecular, prevents the polyketone from being denatured, reduces the broken wire rate of the polyketone fiber, and improves the tensile strength and elongation at break.
[0047] Test Example 2 The polyketone fibers prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to a heat resistance test. The polyketone fibers were heat treated at 200° C. in an air atmosphere for 24 h, and the tensile strength of the polyketone fibers was tested. The tensile strength reduction rate was calculated, and the results were as follows:
[0048] It can be seen from the test results of Test Examples 1 and 2 that the elongation at break and the tensile strength after heat treatment of the polyketone fiber prepared in Comparative Example 3 are significantly lower than those of the polyketone fiber in Example 2, indicating that the use of modified multi-walled carbon nanotubes can significantly improve the elongation at break of the polyketone fiber and reduce the rate of decrease in tensile strength after heat treatment.
[0049] It can be seen from the test results of Test Examples 1 and 2 that the polyketone fiber prepared in Comparative Example 4 has a higher broken wire rate, and the tensile strength, elongation at break, and tensile strength after heat treatment are greatly reduced compared with Example 2; even compared with Comparative Example 3 without adding multi-walled carbon nanotubes, the broken wire rate is higher, and the tensile strength, elongation at break, and tensile strength after heat treatment are lower. This is because the untreated multi-walled carbon nanotubes used are not easy to disperse in the polyketone matrix, causing a large number of multi-walled carbon nanotubes to agglomerate, which seriously affects the properties of the prepared polyketone fiber, such as the broken wire rate, tensile strength, elongation at break, and thermal stability.
[0050] In the present invention, hydroxyl multi-walled carbon nanotubes are reacted with N-isovalerylaminoacetic acid and maleamic acid to prepare modified multi-walled carbon nanotubes, so that the multi-walled carbon nanotubes are uniformly dispersed in a polyketone matrix, the elongation at break of the polyketone fiber is increased, and the toughness of the polyketone fiber is improved; the amide groups introduced into the modified multi-walled carbon nanotubes form hydrogen bonds with the polyketone, the binding force between the multi-walled carbon nanotubes and the polyketone molecules is increased, the denaturation problems such as cross-linking between polyketone molecules can be effectively reduced, the broken wire phenomenon of the polyketone fiber is reduced, the tensile strength of the polyketone fiber and the tensile strength reduction rate after heat treatment are increased, and the thermal stability of the polyketone fiber is effectively improved.
[0051] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing polyketone fiber by wet spinning, characterized in that: The method for preparing polyketone fiber by wet spinning comprises the following steps: preparing raw materials, preparing spinning solution, spinning, and stretching; The preparation method of the raw material comprises the following steps: mixing polyketone, pyrrole copolymer, modified multi-walled carbon nanotube, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50 and powdered phosphite, and then extruding and granulating to obtain a polyketone blend; The preparation of the pyrrole copolymer includes preparing N-vinyl pyrrole, copolymerizing; The copolymerization method comprises dissolving sodium perfluorononenyloxybenzenesulfonate in a hydrochloric acid solution to prepare a sodium perfluorononenyloxybenzenesulfonate solution, then adding N-vinyl pyrrole and pyrrole, introducing ethylene after stirring, and simultaneously dropping a hydrochloric acid-acidified ferric chloride solution, stirring continuously for 24-26 hours under an ice bath condition, washing the sample with water after the reaction is completed, and freeze-drying to constant weight to obtain a pyrrole copolymer; The preparation method of the modified multi-walled carbon nanotubes comprises dissolving N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes and p-toluenesulfonic acid in cyclohexanone, heating to 90-95° C. after ultrasonic oscillation, stirring and reacting at the temperature for 10-12 hours, filtering, washing the filter cake and drying to obtain the modified multi-walled carbon nanotubes.
2. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: In the step of preparing the raw materials, the stirring process temperature is 130-140° C., the stirring rate is 800-1000 rpm, and the stirring time is 8-10 min.
3. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: In the raw material preparation step, the intrinsic viscosity of polyketone is 1-1.5 dl / g; the mass ratio of polyketone, pyrrole copolymer, modified multi-walled carbon nanotube, thermoplastic polyurethane, alkyl sulfonate phenyl ester T50, and powdered phosphite is 100: (5-7): (2-3): (3-5): (0.5-0.8): (0.6-0.8).
4. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: In the step of preparing the pyrrole copolymer, the concentration of the hydrochloric acid solution is 40-45 g / L; the concentration of the sodium perfluorononenyloxybenzenesulfonate solution is 220-230 g / L; the concentration of the ferric chloride solution is 25-30 g / L; and the ethylene introduction rate is 0.2-0.3 L / min.
5. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: In the step of preparing the pyrrole copolymer, the mass ratio of N-vinylpyrrole, pyrrole, ethylene, sodium perfluorononenyloxybenzenesulfonate and ferric chloride is (8-10): (10-12): (2-3): (18-20): (100-120).
6. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: In the preparation step of the modified multi-walled carbon nanotubes, the ultrasonic oscillation time is 20-25 minutes, and the ultrasonic oscillation frequency is 10-12kHz; The mass ratio of N-isovalerylaminoacetic acid, maleamic acid, hydroxylated multi-walled carbon nanotubes, p-toluenesulfonic acid and cyclohexanone is (6-8):(3-4):(40-50):(0.3-0.5):
100.
7. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: The spinning solution is prepared by adding a polyketone blend into a dimethyl sulfoxide solvent to make the polyketone blend have a concentration of 10-12 wt %, stirring and dissolving at 30-35° C. for 30-40 min, degassing under reduced pressure and stirring for 6-7 h, and filtering at 30-35° C. after stirring to obtain the spinning solution.
8. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: In the spinning, the spinning solution is introduced into the spinning assembly by a metering pump, the ejected spinning solution is introduced into a coagulation bath to coagulate into fibers, and then the collected fibers are washed and dried with ethanol to obtain primary fibers.
9. A method for preparing polyketone fiber by wet spinning according to claim 8, characterized in that: In the spinning step, the spinning solution temperature is 90-95°C, the coagulation bath is composed of dimethyl sulfoxide and water, the mass ratio of dimethyl sulfoxide to water in the coagulation bath is 1:(4-5), and the temperature of the coagulation bath is 5-8°C.
10. The method for preparing polyketone fiber by wet spinning according to claim 1, characterized in that: The stretching comprises the following steps: thermally stretching the spun fibers in three stages, wherein the temperature of the primary stretching is controlled at 238-242° C., and the stretching ratio is 6-7 times; after the primary stretching, a secondary stretching is performed, wherein the temperature of the secondary stretching is controlled at 248-252° C., and the stretching ratio is 2-2.5 times; after the secondary stretching, a tertiary stretching is performed, wherein the temperature of the tertiary stretching is controlled at 258-262° C., and the stretching ratio is 1.5-1.8 times; and after the tertiary stretching, polyketone fibers are obtained.